TRADE BUILDINGS "TIM" DURING THE TIMURIDS AND KHANATES - Abdullayev Bahodir Allamurod o'g'li (Web of Journals Publishing, 2025)
This article describes the history of «Tim» markets and their current functions, the restoration of trade routes in the era of Amir Temur and the Timurids, the development of the later commercial buildings and activities of the Timurids and Khans.